2022
DOI: 10.4041/kjod.2022.52.2.123
|View full text |Cite
|
Sign up to set email alerts
|

Remote digital monitoring during the retention phase of orthodontic treatment: A prospective feasibility study

Abstract: Objective To evaluate if a remote digital monitoring system added at the end of orthodontic treatment could positively influence the retention phase by reducing the occurrence of misfit of removable appliances, number of emergency appointments (EA), and orthodontic relapse. Methods Twenty-seven patients who completed active orthodontic treatment were divided into the study and control groups. In addition to the standard chairside follow-up appointments at month 1 (T1), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 37 publications
(52 reference statements)
0
19
0
Order By: Relevance
“…Based on the five journals included in this review, the clinical application of DM can provide several advantages for its users, including facilitating dentists to monitor patients' tooth movements remotely and reducing the number of inoffice visits. In addition, the use of DM can also increase patient compliance in maintaining oral hygiene and using retainers [1,[3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on the five journals included in this review, the clinical application of DM can provide several advantages for its users, including facilitating dentists to monitor patients' tooth movements remotely and reducing the number of inoffice visits. In addition, the use of DM can also increase patient compliance in maintaining oral hygiene and using retainers [1,[3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…The success of orthodontic treatment does not only depend on proper diagnosis and treatment, but also on patient's compliance [1,2]. During orthodontic treatment, several studies have shown a rapid decline in the level of oral hygiene, which may lead to changes in composition of bacteria flora, leading to dental plaque accumulation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations